Tectonic structure, evolution, and the nature of oceanic core complexes and their detachment fault zones (13°20′N and 13°30′N, Mid Atlantic Ridge). (8th April 2017) - Escartín, J.; Mével, C.; Petersen, S.; Bonnemains, D.; Cannat, M.; Andreani, M.; Augustin, N.; Bezos, A.; Chavagnac, V.; Choi, Y.; Godard, M.; Haaga, K.; et al.
Abstract: Microbathymetry data, in situ observations, and sampling along the 13°20′N and 13°20′N oceanic core complexes (OCCs) reveal mechanisms of detachment fault denudation at the seafloor, links between tectonic extension and mass wasting, and expose the nature of corrugations, ubiquitous at OCCs. In the initial stages of detachment faulting and high‐angle fault, scarps show extensive mass wasting that reduces their slope. Flexural rotation further lowers scarp slope, hinders mass wasting, resulting in morphologically complex chaotic terrain between the breakaway and the denuded corrugated surface. Extension and drag along the fault plane uplifts a wedge of hangingwall material ( apron ). The detachment surface emerges along a continuous moat that sheds rocks and covers it with unconsolidated rubble, while local slumping emplaces rubble ridges overlying corrugations. The detachment fault zone is a set of anostomosed slip planes, elongated in the along‐extension direction. Slip planes bind fault rock bodies defining the corrugations observed in microbathymetry and sonar. Fault planes with extension‐parallel stria are exposed along corrugation flanks, where the rubble cover is shed. Detachment fault rocks are primarily basalt fault breccia at 13°20′N OCC, and gabbro and peridotite at 13°30′N, demonstrating that brittle strain localization in shallow lithosphere form corrugations, regardless of lithologies in the detachment zone. Finally, faulting and volcanism dismember the 13°30′N OCC, with widespread present and past hydrothermal activity (Semenov fields), while the Irinovskoe hydrothermal field at the 13°20′N core complex suggests a magmatic source within the footwall. These results confirm the ubiquitous relationship between hydrothermal activity and oceanic detachment formation and evolution. Plain Language Summary: Oceanic detachments are long‐lived faults that are exposed at the seafloor, often showing prominent corrugations. Detailed mapping and inset observations and sampling, using remotely operated and autonomous robots, demonstrate as these fault surfaces are exposed at the seafloor, erosion and deposition of debris cover these faults systematically with a thin layer of rubble, demonstrating that their evolutions intimately linked to surface processes. Locally, the fault itself is exposed, displaying striated fault planes on the flanks of corrugations. A complex, three‐dimensional network of fault planes within the detachment zone defines elongated bodies of rock (corrugations).These detachments also confirm that there is a direct link between detachment formation and hydrothermal activity, as they host both active and inactive hydrothermal fields. Key Points: Oceanic detachment fault corrugations correspond to anastomosing fault slip planes localizing brittle deformation in shallow lithosphere Mass wasting is associated with detachment denudation and blankets its surface though shedding of material at termination Faulting, associated with magmatism and hydrothermalis, terminates detachments, and hydrothermalism linked systematically to detachments